The frequency of trichomonas vaginalis, gardnarella vaginalis and candida ssp. Among infertile men and women with vaginitis - Keleştemur, Neslihan; Kaplan, Mustafa; Özdemir, Enver; Erensoy, Ahmet (Veteriner Fakultesi Dergisi, 2012)
Trichomonas vaginalis, Gardnarella vaginalis and Candida spp. were known as important causes of sexually transmitted infection in developing countries. The prevalence and spectrum of trichomonasis, Gardnarella vaginalis and Candida spp. in infertile men and women with vaginitis are not yet fully elucidated. We analyzed the presence of T. vaginalis, G. vaginalis and Candida spp. in 80 infertile males and 160 females with a diagnosis of vaginitis using wet mount microscopy, Giemsa staining, culture and PCR methods. The specimens were obtained from posterior vaginal fornix in woman and prostatic expression fluid or semen in men. The ages of the men were ranged from 16 to 60 (median±SD, 31±9), and that of women were ranged from 17 to 70 (median±SD; 37±11). Among female patients, G. vaginalis was positive in 110 (68.8%), Candida spp. was positive in 39 (24.4%) and T. vaginalis was positive in 7 (4.5%). Among male patients, G. vaginalis was positive in 20 (25%), Candida spp. was positive in 8 (10%) and T. vaginalis was positive in 3 (3.8%). Our findings suggest that T. vaginalis, G. vaginalis and Candida spp. should be considered for the ethiology of the infertile male patients and female patients with complaints of discharge, pain, dysuria, itching and dry mouth. © 2012, Veteriner Fakultesi Dergisi. All rights reserved.
İnfertil erkek ve vajinitli kadın hastalarda trichomonas vaginalis, gardnarella vaginalis ve candida ssp. Sıklığı
Keywords: Candida spp; Females; Giardia vaginalis; Infertile males; Sexually transmitted diseases; Trichomonas vaginalis